The Unveiling Efficiency Through Flexibility: A New Paradigm for Business Performance at PT Bukit Asam - Suhendra, Chairul; Pefriyadi, Pefriyadi; Ardiles Nur (Takaza Innovatix Labs Ltd., 2023)
This study aims to evaluate the effect of Operational Efficiency Level, Organizational Flexibility Level, and Process Innovation Level on Total Business Performance at PT Bukit Asam (Bengkulu Branch). Multiple regression analysis conducted to examine the effect of Operational Efficiency Level, Organizational Flexibility Level, and Process Innovation Level on Total Business Performance at PT Bukit Asam (Bengkulu Branch) resulted in important findings. Operational Efficiency and Organizational Flexibility significantly and positively influence Total Business Performance, indicating their potential to improve overall business performance. However, Process Innovation did not show a significant influence at the time of analysis. The regression model explained about 65.7% of the variance in Total Business Performance, emphasizing the collective significance of these variables. Nonetheless, about 34.3% of the variation remained unexplained, suggesting the presence of additional influential factors beyond the scope of the model. These findings highlight the importance of prioritizing Operational Efficiency and Organizational Flexibility strategies to improve business performance. The findings also underscore the need for further exploration or broader context consideration of Process Innovation to comprehensively improve business performance. This study assists management in formulating more effective strategies, recognizing the critical factors that impact business performance while acknowledging the complexity in determining the whole.